2020
DOI: 10.1016/j.accpm.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the renin-angiotensin-aldosterone system is associated with Acute Kidney Injury in COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 7 publications
0
40
0
4
Order By: Relevance
“…Specifically, COVID-19-associated ARDS is often treated by increasing positive end-expiratory pressure (PEEP), which leads to increased intrathoracic pressure and can ultimately result in increased renal venous pressure and reduced filtration, which may be further amplified if intra-abdominal pressure is elevated (for example, with fluid overload) 51 . In addition, all forms of positive pressure ventilation can increase sympathetic tone, leading to secondary activation of the renin–angiotensin system 52 , 53 . In the setting of ARDS after shock resolution, patients are often managed with a restrictive fluid strategy.…”
Section: Pathophysiology and Effects Of Treatmentmentioning
confidence: 99%
“…Specifically, COVID-19-associated ARDS is often treated by increasing positive end-expiratory pressure (PEEP), which leads to increased intrathoracic pressure and can ultimately result in increased renal venous pressure and reduced filtration, which may be further amplified if intra-abdominal pressure is elevated (for example, with fluid overload) 51 . In addition, all forms of positive pressure ventilation can increase sympathetic tone, leading to secondary activation of the renin–angiotensin system 52 , 53 . In the setting of ARDS after shock resolution, patients are often managed with a restrictive fluid strategy.…”
Section: Pathophysiology and Effects Of Treatmentmentioning
confidence: 99%
“…SARS-CoV2 has been suggested to modulate the renin-angiotensin-aldosterone system (RAAS). Evidence of activation of the RAAS in patients with COVID-19 who have acute kidney injury, leading to increased sCr, has been reported [ 40 ]. Several studies have also reported that liver damage occurred in severe cases of COVID-19 infection at rates ranging from 58% to 78% [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the viral tropism to the kidneys, acute renal injury was found to be the second most observed COVID-19 complication in the USA (22.2%) [ 77 ] and China (25.2%) [ 67 ]. Thus, there is compelling evidences that patients with acute kidney injury at admission exhibit activation of RAAS, as documented by higher plasmatic renin and aldosterone levels and lower urinary sodium levels in patients with acute kidney injury [ 109 ], as well as the association of plasmatic aldosterone and C-reactive protein levels and COVID-19 severity [ 110 ]. Since hypokalaemia was found to be prevalent in patients with COVID-19 pneumonia (~ 30%) and is an indicator of RAAS activity, it was suggested that hypokalaemia could be used as a surrogate marker of COVID-19 progression and an independent risk factor for invasive mechanical ventilation requirement [ 111 ].…”
Section: Comorbidities and Ace/ace2 Balance Disruptionmentioning
confidence: 99%